What is mental disorder? an essay in philosophy, science, and values - Bolton, Derek (Oxford : Oxford University Press, 2008)
The effects of mental disorder are apparent and pervasive, in suffering, loss of freedom and life opportunities, negative impacts on education, work satisfaction and productivity complications in law, institutions of healthcare, and more. This book tackles the problems involved in the definition and boundaries of mental disorder.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mental illness -- Philosophy